(untitled) (International Journal of Current Engineering and Technology, 2014)
Digital audio watermarking is an important and popular technique along the original musical audio content producers. Watermarks can be utilised as evidence for proving the ownership. Musical audio can be characterized by the common characteristics shared in low-level, mid-level and high-level features. These characteristics typically are timbre, temporal, rhythmic, pitch, harmony, genre, mood, instrument, and many more which can be extracted from the music. Automatic musical audio feature extraction is utilised for identifying genre and its respective utilization can be carried out in audio watermarking area so as to improve the performance. The paper describes the techniques developed till date for audio watermarking and audio feature extraction techniques in brief.